The Effectiveness of Provisioning Bit Fruit Juice on Increasing Hb Levels for Pregnant Women with Anemia in H. Syahruddin Clinic Tanjung Balai - Ustifina Hasanah Hasibuan; Herviza Wulandary; Noprisanti (Science Midwifery, 2022)
Anemia is a condition where there is a decrease in hemoglobin, hematocrit, and erythrocyte counts below normal values. Severe anemia if Hb < 8 g/dl, mild anemia if Hb > 8-11 g/dl and normal in pregnant women Hb > 11 g/dl. It is known the effect of giving beetroot juice on hemoglobin levels of pregnant women with anemia at the H. Syahruddin Clinic, Tanjung Balai. Pre-experimental action with One group pretest-posttest design. The sample is 20 people, the sampling technique used is purposive sampling. Data collection using observation sheets and data analysis used is the T-dependent test. It is known that the average value of hemoglobin levels before administration and the average value of hemoglobin levels after administration of fruit juice is 0.021. There is an effect of giving beetroot juice to increase hemoglobin levels in pregnant women with anemia p value = 0.000 < = 0.005. Pregnant women can consume beetroot juice regularly to prevent anemia and consume foods that contain vitamin C.